Meaningfulness Of Life For Elderly Age In An Orphanage Rumah Singgah Pajang - Hanifa Qurrata Ayunin, Hinda; Riskiana Putri, Dhian (Profesional Muda Cendekia Publishing, 2024)
Research Aims: The purpose of this research is to see the meaningfulness of life in the elderly. The ben-efits that are expected to be possessed in this research include theoretical benefits, which are expected to become reference material for the development of developmen-tal psychology, especially psychogerontology and practical benefits to become refer-ence material for psychologists, therapists, counselors, companions, and readers in an effort to increase the meaning of life in the elderly in general and in the elderly living in nursing homes in particular. Design/methodology/approach: The subject criteria for the study were elderly people who could still be invited to communicate and were in good general condition. These crite-ria are determined on the basis of consideration because this research was conducted using interviews as a method of collecting data. Research Findings: The results of this study indicate that the elderly have a good meaningful life. Theoretical Contribution/Originality: This research highlights unique aspects of that specific context, such as the lived experiences of older people in care homes and how it affects their meaning of life. This can make a valuable contribution to our understanding of how meaning in life is understood and experienced by older people in care homes, and provide new insights that can form the basis for the development of better care programmes.